Dampak Pengungkapan CSR Terhadap Value Perusahaan - Hartiningsih, Tri (Graha Akuntansi, 2021)
This study aims to determine the effect of Corporate Social Responsibility on Corporate Value with Corporate Governance as a moderating variable in manufacturing companies. The analytical method used is factor analysis to reduce the four moderating variables, namely managerial ownership, institutional ownership, the proportion of independent commissioners and the number of audit members, then multiple linear regression and classical assumption tests are performed. The results showed that Corporate Social Responsibility Disclosure had a positive effect (0.794) on Firm Value and there was no significant relationship 0.433 > α (0.05), the direction of a positive relationship means that the smaller the level of CSR Disclosure, the lower the level of Corporate Value due to the quality of CSR disclosure in the studied companies listed on the IDX is very low and has not followed the applicable standards. Corporate governance results show a positive effect (0.003) on firm value and have an insignificant relationship 0.9997 < α (0.05). While the results of Corporate Social Responsibility Disclosure on Corporate Value with Corporate Governance as a moderating variable have a positive effect (2.457) and there is a significant relationship 0.020 > α (0.05), there is a positive relationship and a significant influence shows that Corporate Governance as a moderating variable can strengthen the influence Corporate Social Responsibility towards Corporate Values